Flexibility, torque and kick performance in soccer: Effect of dominance - Oliveira, A.S.C.; Barbieri, F.A.; Gonçalves, M. (Science & Sports, 2013)
Aim: The aim of this study was to evaluate the knee flexor and extensor torques in isometric contractions, comparing the H:Q ratios, flexibility and maximal kick between dominant (DL) and non-dominant (NDL) limb of soccer players (SG) and active people (AG). Methods: Subjects performed maximal instep kicks with each limb, flexibility tests and maximal isometric voluntary contractions of the knee flexion and extension at 45° and 90° to determine peak torque of the DL and NDL. Knee flexion torque was divided by the knee extension torque to calculate torque ratios (H:Q ratio). Results: The flexibility and maximal kick in SG was significantly higher than in AG for both the DL and NDL (P < 0.05). The maximal kick of DL was significantly higher than in NDL in SG (P < 0.01). Knee flexion torque in SG was significantly higher than in AG in the DL (P < 0.05), and the H:Q ratio was similar between AG and SG. Conclusion: Dominance related differences were evident in the flexor torque and maximal kick for SG, probably related to the asymmetric demand in trainings, which present no effect on the flexibility.